Correlates of 1‐Year Incidence of Urinary Incontinence in Older Latino Adults Enrolled in a Community‐Based Physical Activity Trial. Issue 4 (11th March 2014) - Morrisroe, Shelby N.; Rodriguez, Larissa V.; Wang, Pin‐Chieh; Smith, Ariana L.; Trejo, Laura; Sarkisian, Catherine A.
<x xml:space="preserve">Abstract</x> The prevalence of urinary incontinence (UI) among older urban Latinos is high. Insight into etiologies of and contributing factors to the development of this condition is needed. This longitudinal cohort study identified correlates of 1‐year incidence of UI in older community‐dwelling Latino adults participating in a senior center–based physical activity trial in Los Angeles, California. Three hundred twenty‐eight Latinos aged 60 to 93 participating in Caminemos, a randomized trial to increase walking, were studied. Participants completed an in‐person survey and physical performance measures at baseline and 1 year. UI was measured using the International Consultation on Incontinence item: "How often do you leak urine?" Potential correlates of 1‐year incidence of UI included sociodemographic, behavioral, medical, physical, and psychosocial characteristics. The overall incidence of UI at 1 year was 17.4%. Incident UI was associated with age, baseline activity of daily living impairment, health‐related quality of life (HRQoL), mean steps per day, and depressive symptoms. Multivariate logistic regression models revealed that improvement in physical performance score (odds ratio (OR) = 0.69, 95% confidence interval (CI) = 0.50–0.95) and high baseline physical (OR = 0.60, 95% CI = 0.40–0.89) and mental (OR = 0.62, 95% CI = 0.43–0.91) HRQoL were independently associated with lower rates of 1‐year incident UI. An increase in depressive symptoms at 1 year (OR = 4.48, 95% CI = 1.02–19.68) was independently associated with a higher rate of incident UI. One‐year UI incidence in this population of older urban Latino adults participating in a walking trial was high but was lower in those who improved their physical performance. Interventions aimed at improving physical performance may help prevent UI in older Latino adults.